Analisis Efisiensi Teknis Bank Syariah Indonesia - Hananto, Bernad; Ari Mulyono Hadi; Iin Masriah; Azmy Muhammad Habiby; Asih Sugiyanti (DPPM Universitas Pelita Bangsa, 2024)
In early 2021 Bank Syariah Mandiri, BNI Syariah and BRI Syariah merged to become Bank Syariah Indonesia, this merger of Islamic banks is one of the government's efforts to respond to Islamic economic growth in Indonesia, this research was made to compare the technical efficiency of Indonesian Syariah Banks in the early period merger and the pre-merger period, using the non-parametric Data Envelopment Analysis method, the efficiency revealed includes the function of the bank as a mediator and the function of the bank as a producer that generates income for the sahibul maal both third parties and shareholders, this study reveals that the bank resulting from the merger in year 2 has a significant increase in Total Assets where this increase is in line with the increase in Temporary Sirkah Funds, Wadiah Fund Deposits, and Equity. Profit before Zakat and Tax in year 2 of the merger increased 111% compared to 2019. In 2021 when the bank not yet merged efficiency level of 97% related to its function as a revenue generator, banks in the first and second years after the merger the bank has an efficiency rate of 100%, both as an intermediary and also as a profit earner for third parties and shareholders.